2015
DOI: 10.1289/ehp.1409276
|View full text |Cite
|
Sign up to set email alerts
|

Ambient PM 2.5 , O 3 , and NO 2 Exposures and Associations with Mortality over 16 Years of Follow-Up in the Canadian Census Health and Environment Cohort (CanCHEC)

Abstract: BackgroundFew studies examining the associations between long-term exposure to ambient air pollution and mortality have considered multiple pollutants when assessing changes in exposure due to residential mobility during follow-up.ObjectiveWe investigated associations between cause-specific mortality and ambient concentrations of fine particulate matter (≤ 2.5 μm; PM2.5), ozone (O3), and nitrogen dioxide (NO2) in a national cohort of about 2.5 million Canadians.MethodsWe assigned estimates of annual concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
319
12
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 476 publications
(366 citation statements)
references
References 32 publications
23
319
12
3
Order By: Relevance
“…Also consistent with our RR estimates, a large Canadian-based cohort study estimated a hazard ratio of 1.03 for trachea, bronchus and lung cancers due to PM 2.5 exposure. 17 Using our RR estimates, we estimated that 1.87% (36 cases) to 5.69% (111 cases) of incident lung cancer in Alberta in 2012 were attributable to PM 2.5 exposure. Norman and colleagues 18 completed a similar study in South Africa using the same methods as in the current study and estimated that 5.1% of mortality from cancers of the trachea, bronchus and lung in adults could be attributed to outdoor air pollution (PM 2.5 and PM 10 ), which is more consistent with our sensitivity analysis results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also consistent with our RR estimates, a large Canadian-based cohort study estimated a hazard ratio of 1.03 for trachea, bronchus and lung cancers due to PM 2.5 exposure. 17 Using our RR estimates, we estimated that 1.87% (36 cases) to 5.69% (111 cases) of incident lung cancer in Alberta in 2012 were attributable to PM 2.5 exposure. Norman and colleagues 18 completed a similar study in South Africa using the same methods as in the current study and estimated that 5.1% of mortality from cancers of the trachea, bronchus and lung in adults could be attributed to outdoor air pollution (PM 2.5 and PM 10 ), which is more consistent with our sensitivity analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…We will improve on the present analyses by considering more pollutants such as nitrogen dioxide and using measures of air pollution with accurate spatial and temporal properties, such as those from the Canadian Census Health and Environment Cohort presented in the recent work of Crouse and colleagues. 17 We assumed that the impact of PM 2.5 on lung cancer is uniform across tobacco consumption groups. Given the clear association between tobacco use and lung cancer, if this assumption is not true, our population attributable risk estimates may be an over-or underestimation for certain tobacco consumption groups.…”
Section: Limitationsmentioning
confidence: 99%
“…Positive associations were observed with cardiometabolic but not respiratory mortality in multipollutant models adjusted for PM 2.5 and NO 2 in the Canadian CanCHEC study (10). There were no data on potential individual-level behavioral confounding factors, including cigarette smoking, in either study.…”
mentioning
confidence: 82%
“…Epidemiological studies have shown positive associations between air pollutants such as particulate matter of aerodynamic diameter less than 10 µm (PM 10 ), nitrogen dioxide (NO 2 ), sulphur dioxide (SO 2 ), ozone (O 3 ) and carbon monoxide (CO) and adverse health outcomes (Goldberg et al, 2013;Crouse et al, 2015;Fischer et al, 2015;Liu et al, 2015;Wong et al, 2015;Yorifuji et al, 2016). Many studies have been conducted to assess the health impacts of air pollution in various cities of the world (Boldo et al, 2006;Fattore et al, 2011;Orru et al, 2012;Allen et al, 2013), including Iranian cities (Naddafi et al, 2012a;Gholampour et al, 2014;Ghozikali et al, 2016;Mohammadi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%